The association between skeletal muscle mass and functional capacity outcomes in Chinese older adults: a national community-based study - Chen, Lin; Lu, Xiaoqiang; Zhu, Zhongxin (Frontiers in Public Health, 2025)
BackgroundMaintaining functional independence in older adults is a critical public health objective. Although skeletal muscle mass is recognized as a key contributor to functional capacity outcomes, the exact relationship between them among community-dwelling older adults requires further investigation.MethodsThis cross-sectional study analyzed data from 13,322 participants aged ≥65 years from the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS). Appendicular skeletal muscle mass index (ASMI) was calculated using a validated anthropometric equation, while functional capacity outcomes were assessed using basic and instrumental activities of daily living (BADL/IADL) scores. Multivariable linear regression, generalized additive models, and threshold effect analysis were employed to evaluate associations, with adjustments for demographic, socioeconomic, lifestyle, and comorbidity factors.ResultsIn fully adjusted models, ASMI showed significant inverse associations with both BADL score (β = −0.072, 95% CI: −0.103 to −0.042) and IADL score (β = −0.225, 95% CI: −0.290 to −0.159). Threshold effect analysis revealed sex-specific inflection points: below 6.2 kg/m2 in men and 5.2 kg/m2 below in women, ASMI was negatively associated with BADL/IADL scores, whereas above these thresholds, the associations weakened or reversed. Subgroup analyses indicated stronger effects among men, urban residents, and those with stroke or cardiovascular disease.ConclusionMuscle mass demonstrates sex-specific, non-linear associations with functional capacity outcomes in older adults, identifying critical thresholds that may inform targeted strategies to preserve independence.